Computational intelligence: It’s application in digital watermarking - Olanrewaju, Rashidah Funke; Khalifa, Othman Omran; Abdul Latif, Khairun Nisaa’ (IDOSI Publications, 2013)
Impersonation and piracy of intellectual properties remain an indispensable problem across the globe. Currently over millions of digital songs, images and videos are copied illegally during file-sharing over the networks, costing loss of revenue to multimedia industries. Digital Watermarking (DW) is an efficient method that embeds an imperceptible message in digital object to protect copyright and authenticate digital media in order to prevent forgery and impersonation. Computational Intelligence (CI); a well-established paradigm is currently gaining attraction in the field of information hiding due to its ability to solve and improve complex problems encountered. CI has been applied in digital watermarking to improve performance in order to curb piracy. This paper brings to view of computational intelligence techniques specifically the Artificial Neural Network (ANN); generalizations of mathematical models based on biological nervous systems and its applications in digital watermarking. Mathematical model of ANN in relation to digital watermarking is indentified, elucidated and simplified. Results of image watermarking using both ANN and no ANN were compared. It was found that ANN based watermarking outperformed the No ANN algorithm in terms of imperceptibility. It is anticipated that this paper will serve as a launch pad for researchers interested in intelligent watermarking.